Association of CD4+ radiation-induced lymphocyte apoptosis with fibrosis and telangiectasia after radiotherapy in 272 breast cancer patients with >10-year follow-up - Veldwijk, Marlon Romano; Sperk, Elena; Giordano, Frank Anton; Kirchner, Anne; Behrens, Sabine; Wenz, Frederik; Chang-Claude, Jenny; Herskind, Carsten; Gürth, Nicole (Clinical cancer research, 2019)
Purpose: Radiation-induced lymphocyte apoptosis (RILA) has been suggested as a predictive assay for adverse late reactions after radiotherapy. Thus, low RILA values of T-lymphocyte subpopulations have been associated with increased risk for various endpoints at 2 to 3 years of follow-up. The purpose was to test if such associations persist for specific endpoints (subcutaneous fibrosis, telangiectasia) in breast cancer patients with at least 10 years of follow-up.Experimental Design: Two hundred and seventy-two female patients who had received breast-conserving therapy within the German ISE study were included (median follow-up: 11.6 years). Radiotherapy-induced side effects were scored according to the Late Effects in Normal Tissues-Subjective, Objective, Management, and Analytic (LENT-SOMA) classification system. RILA in the CD4+, CD8+, and natural killer (NK) subpopulations from peripheral blood was analyzed by flow cytometry. Multivariate predictive modeling was performed including relevant clinical risk factors. - Results: Low CD4+ RILA was associated with increased risk for both fibrosis (P = 0.011) and telangiectasia (P < 0.001). For fibrosis, the association was stronger outside the surgical area (Fibout; P = 0.004) than within (Fibin; P = 0.17). Predictive multivariate modeling including clinical risk factors yielded OR of 3.48 (95% confidence interval, 1.84-6.58) for any fibrosis and 8.60 (2.71-27.3) for telangiectasia. Addition of CD4+ RILA to the clinical variables improved discrimination (c statistics) from 0.62 to 0.68 for any fibrosis, 0.62 to 0.66 for Fibin, 0.61 to 0.69 for Fibout, and from 0.65 to 0.76 for telangiectasia. CD8+ and NK RILA were not significantly associated with radiotherapy-related late reactions. - Conclusions: The results provide first evidence that low CD4+ RILA is associated with increased subcutaneous fibrosis and telangiectasia even after 10 years. This supports the potential usefulness for predicting individual clinical risk.